Por uma educação ambiental crítica na formação inicial de professores/as: possibilidades emancipatórias em licenciaturas da UFPB - Lopes, Theóffillo da Silva (2022)
This study was developed in a qualitative approach to research in education on the practice and discussions of Critical Environmental Education in the Initial Training of Teachers. From the perspective of social demands on education, from the new scientific, philosophical, technological and theoretical knowledge about the environmental problems that humanity faces today, and how this knowledge and its problems need to be present in the training of professionals who will work in the practices education, this work aimed to analyze the possibilities of re-signification of conceptions/actions on Environmental Education, through a process of complementary training, developed in a critical way in the initial training of teachers of the Licentiate courses in Social Sciences, History, Geography and Biological Sciences at the Federal University of Paraíba, João Pessoa Campus. In this sense, in coherence with critical premises of research in education, the study had the Dialectical Historical Materialism as its epistemological orientation, understanding the non-neutral character of education and investigation and was anchored in an Action Research, carried out from a course of complementary training on Critical Environmental Education, offered to students of the degrees investigated here, guaranteeing their adherence and participation, in a practical-interpretative way and through critical actions. In order to carry out the research objectives, the Pedagogical Projects of the Courses (PPC) were also analyzed and a semi-structured questionnaire was applied to the research participants. The analysis of the results was carried out from the Content Analysis in a critical perspective, which walks with research assumptions as a real construction of society and expression of human existence. The results show that the environmental aspects present in the PPC, which present all the environmental issues, are concentrated in the optional subjects of the courses, while the compulsory subjects focus on natural aspects. These conflicting characteristics found in the curricula are reflected in the students' conceptions, revealing that, even understanding the purpose of EE in a critical way, their conceptions about concepts, objectives, thematic approach and contents and themes to be worked on, still walk in a EE's Conservative trend. In another way, it was possible to verify that critical practices, which include the educational praxis of action-reflection-action, could give rise to new conceptions, collectively building new attitudes towards oneself, the world, the other and nature. Dialectically, understanding the character of historicity, becoming and the contradictory of concrete reality, it is considered the need for a problematizing environmental educational practice in the initial training of teachers, which is anchored in the praxis and dialectics existing in education and in the problems environmental issues, breaking with positivist, traditional and pragmatic paradigms, consistent with theoretical, epistemological, methodological and ontological foundations of critical theories of education. The fulfillment of the objectives of this research, together with the theoretical and empirical contributions, validate the thesis that a Critical Environmental Education, historically situated, in the initial formation of teachers/as, from the critical reflection and the collaboration in the production of knowledge, propitiates changes of conceptions in the individuals involved, regarding their positioning before themselves and the world and the development of Environmental Education.